Corporate derivatives and ownership concentration: Empirical evidence of non-financial firms listed on Pakistan Stock Exchange - Affaf Asghar Butt; Main Sajid Nazir; Hamera Arshad; Aamer Shahzad (Journal of Risk and Financial Management, 2018)
Risk management has been gaining tremendous fame for the last couple of years. Firms in developed and developing countries are facing a variety of risks, i.e., foreign exchange risk, interest rate risk, commodity price risk, and equity risk. It calls for such hedging techniques that mitigate this risk level, thus, allowing corporations to enjoy a solid return. This paper draws attention to a new determinant of hedging, i.e., the role of ownership concentration in risk management using derivative instruments. For this purpose, a sample data of 101 non-financial firms listed on the Pakistan Stock Exchange (PSX) for six years, ranging from 2010-2016, is used. The Mann-Whitney test for difference in users and no-users is applied along with logistic regression to check the effect of ownership concentration on derivative usage. The finding of this study reveals that concentrated owners are less likely to use derivatives for hedging purposes due to concentrated owners' interests (top five shareholders & largest shareholder, family owners). Whereas, executives are more likely to engage in the use of derivatives to increase the value of their stocks. However, associated companies are significantly less involved in hedging activities. These results are extremely advantageous for policymakers in corporations to create a more stable corporate environment.
Keywords: 330; ownership concentration; derivatives usage; hedging